2013
DOI: 10.3945/an.113.004648
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Fatty Acid Trafficking: Multiple Forks in the Road

Abstract: The liver plays a unique, central role in regulating lipid metabolism. In addition to influencing hepatic function and disease, changes in specific pathways of fatty acid (FA) metabolism have wide-ranging effects on the metabolism of other nutrients, extra-hepatic physiology, and the development of metabolic diseases. The high prevalence of nonalcoholic fatty liver disease (NAFLD) has led to increased efforts to characterize the underlying biology of hepatic energy metabolism and FA trafficking that leads to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 232 publications
(238 reference statements)
2
99
0
Order By: Relevance
“…infection mouse model. This is consistent with the known critical role of the liver in uptake of free fatty acids, fatty acid metabolism, and lipid trafficking including the assembly of very low density lipoprotein (34). Furthermore, pulmonary surfactant, which also contains an array of host-derived fatty acids, may play a role in tissue-specific activation of T7SS genes in host lungs (10), suggesting that this mechanism may be relevant in S. aureus pneumonia as well.…”
Section: Discussionsupporting
confidence: 84%
“…infection mouse model. This is consistent with the known critical role of the liver in uptake of free fatty acids, fatty acid metabolism, and lipid trafficking including the assembly of very low density lipoprotein (34). Furthermore, pulmonary surfactant, which also contains an array of host-derived fatty acids, may play a role in tissue-specific activation of T7SS genes in host lungs (10), suggesting that this mechanism may be relevant in S. aureus pneumonia as well.…”
Section: Discussionsupporting
confidence: 84%
“…In the liver, it is thought that the primary source of TAG is via the glycerol-3-phosphate (G3P) pathway, that generates DAG (Coleman and Mashek 2011; Mashek 2013) which serves as a substrate of DAG transferases 1 and 2 (Dgat1/2). However, it is becoming evident that the MAG pathway [ie.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is becoming evident that the MAG pathway [ie. generation of DAG from MAG via MAG transferases 1 and 2 (Mogat1/2 in mice)], may be a relevant pathway in NAFLD (Hall, et al 2012; Mashek 2013). Examination of the expression of key genes involved in TAG synthesis revealed there was an overall inhibitory effect of aLivPPARĪ³kd on the expression of Mogat1 (Supplemental Table 1) that reached significance with age and HF feeding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that both Pu-erh tea and theabrownin suppressed lipid accumulation and slowed the rate of fatty degeneration in liver tissues [18,28]. The uptake of free fatty acids from the diet has been reported as one of the primary sources of liver-derived fatty acids [32]. In this study, we observed that the expression levels of several genes involved in fatty acid synthesis, such as pparĪ±, pparĪ³, ampk, srebp1 and acc, were significantly decreased in the OTP group compared with the HFD group (Fig.…”
Section: Discussionmentioning
confidence: 98%